Product quality dimensions ranking: The preference of national motorcycle brand customers / Anita Abu Hassan...[et al.] - Abu Hassan, Anita; Shaharudin, Mohd Rizaimy (Universiti Teknologi MARA, Kedah, 2011)
This study is about the findings on the perception of the customers towards the quality level of products of a Malaysian national motorcycle/scooter brand based on the eight quality dimensions framework. It helps in generalizing the standing of the product quality attributes among motorcycle/scooter customers in Malaysia which is crucial in determining the factors of selecting motorcycle/scooter products in the market. Large numbers of studies in the past have mentioned consumers' ambiguity about the definition and understanding of quality. Hence, it is difficult to meet the customers' expectation on quality since their understandings is varied and inconsistent. In this study, the result shows that conformance to specification dimension was the highest rating in associating high product quality as compared to the rest. On the other hand, customers have rated special feature dimension as the lowest factor in deciding to purchase the national motorcycle/scooter brand.